Deaths, infections, and herd immunity in the COVID-19 pandemic: A comparative study of the strategies for disease containment implemented in Peru and the United Kingdom - Jeel Moya-Salazar; Betsy Cañari; Nahomi Zuñiga; Alexis Jaime-Quispe; Victor Rojas-Zumaran; Hans Contreras-Pulache (Revista de la Facultad de Medicina)
Introduction: In light of the threat posed by the COVID-19 pandemic, most countries have implemented several containment and prevention measures to slow down the rapid spread of the disease.